Bioimpedance and bone fracture detection: A state of the art. (July 2019) - Dell'Osa, A H; Felice, C J; Simini, F
Abstract: Bioimpedance measurements are used increasingly in health applications because bioelectric parameters have been associated with anatomical and physiological properties, thus enabling to distinguish medical conditions. For bone fracture diagnostics, nevertheless, there is no established non-invasive method. Ex vivo studies and In vivo bioimpedance procedures, both invasive and non-invasive, on mammalians long bones are associated with promising results. In this work, out of a total of 568 papers, we reviewd 59 articles that mention long bone integrity by electric properties, be it Bioimpedance Analysis, Electrical Impedance Spectroscopy or Electrical Impedance Tomography. The papers are described in three sections, "Ex vivo measurements", "In vivo invasive measurements" and "In vivo non-invasive measurements". This review allows to establish the basics to planning the development of new technology to detect bone fracture via bioimpedance measurements.